Determinasi Beban Kerja dan Budaya Kerja Terhadap Kepuasan Kerja Karyawan di PT Erima Baja Jaya - Achmad Romadhon; Jumawan Jumawan; Hadita Hadita; Alfonso Lande; Heru Tian Sanjaya; Bima Dwi Mardika; M. Rafli Hermawan (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
This research aims to determine the influence of workload and work culture on employee job satisfaction at PT Erima Baja Jaya. This research uses descriptive quantitative methods. The analytical tool used is SEM SmartPLS 3.0. The data used in this research is primary data, obtained from a questionnaire created via Google Forms and distributed to employees of PT Erima Baja Jaya. The population in this study was 91 people with a sample of 40 people. The sampling technique used was simple random sampling. The tests carried out in this research were reliability, validity, t test and f test. The results of this research are: 1) Workload has no positive and insignificant effect on employee job satisfaction at PT Erima Baja Jaya and 2) Work culture has no positive and insignificant effect on employee job satisfaction at PT Erima Baja Jaya.